Groundwater for irrigation in Lao PDR - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2017)
Groundwater can provide irrigation for rural communities where surface water is absent or unreliable. Technical, institutional and capacity limits have prevented rural communities from using groundwater for irrigation, and researchers have not demonstrated how to extract and use groundwater effectively for agriculture. A recent Australian-funded research project addresses each of these obstacles. This policy brief draws from the project’s findings and lessons to present policy options for irrigation using groundwater. It also suggests how to strengthen capacity and promote cross-sector coordination, and identifies priority areas for further research for redevelopment. This policy brief does not cover wider groundwater governance issues; another policy paper, currently in the advanced stages of preparation, will present them.